Bimbingan Konseling Islam dengan Rational Emotve Behavior Theraphy dalam Menangani Perilaku Agresif Anak di SD Al-Falah Assalam Tropodo Sidoarjo - Fahmi, Lukman; Basyid, Abd. (Proceedings of International Conference on Da'wa and Communication, 2019)
In this research, the researcher tries to review a method of counseling guidance in the aggressive behavior handling of a 4th-grade elementary school in SD Al–Falah Assalam Tropodo Sidoarjo, the method is Rational Emotive Behavior Therapy (REBT). A method that has developed in the 1950’ by an American Physiologist, Albert Ellis, REBT completely focus on personality changing effectively into better behavior of course. Wherein outline the behaviors affected by two main factors; Internal factor which directly related with descant or gen whereas external factor which directly related with environments place the individual living. The research uses a qualitative descriptive approach, in which the main subject of research is a 4th-grade student who is identified as aggressive behavior having. According to the case, this research purposed to dig information on whether the student just to be aggressive in school or in-home instead, what factors affected the aggressive behavior, and then apply the REBT method as a solution to the aggressive behavior handling. Expecting from this research is the result of research that could be used to handle aggressive behaviors for other students and also used as a reference in the research of other counseling guidance.